Adoption of multimedia technology for learning and gender difference. (March 2019) - Park, ChongWoo; Kim, Dong-gook; Cho, Sunyoung; Han, Hyo-Joo
Abstract: While more educators are increasingly using multimedia technology for online and blended learning, there has not been much research on whether and how multimedia technology is accepted and used by learners. In this study, we examine the adoption of multimedia technology for online and blended learning. In order to better understand its adoption mechanism, we propose an integrated model, which extends the technology acceptance model with task technology fit theories. Furthermore, this study investigates gender difference as a moderator in the integrated model. The proposed research model has been assessed with the data collected from three online and blended classes where multimedia technology has been used for learning. The results obtained from the partial least squares analysis show that multimedia technology positively affects the user's perception of fit in learning, which in turn positively affects the adoption of multimedia technology for learning. In addition, the integrated model increases the explanatory power of the final dependent variable, actual adoption of multimedia technology. We also found the moderating effect of gender difference in the adoption of multimedia technology for learning. Highlights: Multimedia is effective for learning, but its adoption mechanism has received less attention. An integrated model is proposed to explain the multimedia adoption behavior for learning. Individual characteristics such as prior experience affect the multimedia adoption. Gender difference plays a role as a moderator in the multimedia adoption for learning.